Discovery of Single Nucleotide Polymorphisms for Resistance to Abnormal Vertical Growth in Macadamia - Zakeel, Mohamed Cassim Mohamed; Alam, Mobashwer; Geering, Andrew D. W.; Topp, Bruce; Akinsanmi, Olufemi A. (Frontiers in Plant Science, 2021)
Abnormal vertical growth (AVG) syndrome is a serious threat to the Australian macadamia industry as it decreases the yield of nuts by as much as 70% per annum. A lack of information on the cause of AVG has hindered the development of an effective disease management strategy. Discovery of genetic markers associated with disease resistance can be used as tool for rapid selection of elite cultivars, hence helps in efficient disease management. Differences in field susceptibility of macadamia cultivars provide an opportunity for discovery of genetic markers that are associated with host resistance. REML mixed model analysis was performed to estimate the AVG rating of 51 cultivars from multiple origins using phenotypic data from 359 trees planted in four trial sites. Most of the Hawaiian cultivars were found as susceptible, while selections from the Australian macadamia industry breeding program were predominantly resistant. All the cultivars were genotyped for 13,221 DArTseq-based single nucleotide polymorphism (SNP) markers. An association analysis was performed to identify markers associated with AVG resistance and discovered 10 SNP markers that were significantly correlated with AVG resistance. PCR and Sanger sequencing of two arbitrarily selected SNPs validated the association of the markers with AVG resistance. Two SNPs associated with AVG resistance appeared to be introgressed from Macadamia tetraphylla through interspecific hybridization. The confirmed two SNPs would be useful for screening macadamia germplasm in marker-assisted selection in macadamia breeding.